1995
DOI: 10.1111/j.1699-0463.1995.tb01133.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of heparan sulphate‐binding activity of Helicobacter pylori bacteria in their adhesion to murine macrophages

Abstract: M., Paziak-Domanska, B., Rudnicka, W. & Wadstrom, T. The role of heparan sulphatebinding activity of Helicobacter pylori bacteria in their adhesion to murine macrophages. APMIS 103: 469474, 1995.The aim of this study was to determine the role of heparan sulphate (HS)-binding activity of Helicobucter pylori microbes in their adhesion to and ingestion by inflammatory peritoneal macrophages. Two H . pylori strains expressing sialic acid-specific haemagglutinins but differing in the expression of heparan sulphate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…According to previously published data, heparin showed optimal inhibition of H pylori adhesion at a concentration of 1 mg/ml [10]. FITC labelled bacterial suspensions was mixed with equal volumes of RPMI alone or with polysaccharides at a concentration of 1.25 mg/ml, agitated for 1 h at 37°C and added to a macrophage monolayer in relation 50 CFU per one macrophage.…”
Section: Competitive Binding Adhesion Assaymentioning
confidence: 97%
See 1 more Smart Citation
“…According to previously published data, heparin showed optimal inhibition of H pylori adhesion at a concentration of 1 mg/ml [10]. FITC labelled bacterial suspensions was mixed with equal volumes of RPMI alone or with polysaccharides at a concentration of 1.25 mg/ml, agitated for 1 h at 37°C and added to a macrophage monolayer in relation 50 CFU per one macrophage.…”
Section: Competitive Binding Adhesion Assaymentioning
confidence: 97%
“…In the present study we chose the murine macrophage cell line J774A.1 since H. pylori was shown to adhere strongly to these cells [9,10]. The macrophages were inoculated with EHS pretreated with different polysulphated agents (heparin, heparan sulphate, chondroitin sulphate, dextran sulphate and fucoidan).…”
Section: Competitive Inhibition Of Ehs Adhesion To Phagocytes By Polymentioning
confidence: 99%
“…H. pylori binding is complex and has been comprehensively reviewed by Karlsson [137]; binding ligands include 10 separate carbohydrate specificities. Binding to sialic acid [59], sulphate lipids [138], heparan sulphate [67, 139], fucose [140,141], mucin [142], ganglio glycolipids [143], lactosylceramide [144], monhexylceramides [145], glycosphingolipids [146], phosphlipid, phosphatidylethanolamine [147], Lewis b oligosaccharide [148] and blood group antigens [149, 150] has been demonstrated.…”
Section: H Pylori Adhesionmentioning
confidence: 99%
“…Such phenomena may in part explain why H. pylori is a slow pathogen [17,18] that can survive in the gastric mucosa for decades in patients with chronic type B gastritis. Chmiela et al [19] demonstrated that H. pylori also used heparan sulphate-binding activity in its adhesion to murine peritoneal macrophages.…”
Section: Introductionmentioning
confidence: 99%